The Relationship Between Maternal Age and Parity with the Incidence of Low Birth Weight - Novizahanis; Desi Ernita Amru; Roza Erda (CV. CENDIKIA JENIUS INDONESIA, 2025)
Low Birth Weight (LBW) is an important indicator in maternal and neonatal health as it contributes to increased infant morbidity and mortality. In Batam City, the incidence of LBW in 2024 was 388 out of 23,424 live births, or 1.7% of LBW cases across 21 Public Health Centers. This study was conducted at UPT Batu Aji Public Health Center from October 10–14, 2025. The aim of this research was to determine the relationship between maternal age and parity with the incidence of Low Birth Weight (LBW) in the working area of UPT Batu Aji Public Health Center, Batam City, in 2025.This study employed a quantitative method with a cross-sectional approach. The sampling technique used was Systematic Random Sampling, with 260 samples drawn from a population of 742. Data collection was carried out using a checklist form, and data analysis was performed using the chi-square test. The results showed that the incidence of LBW was higher among mothers aged <20 years (66.7%) and >35 years (17.0%), as well as among primiparous mothers (32.7%) and grand multiparous mothers (22.6%). The chi-square test for maternal age and parity revealed a p-value <0.05. Conclusion: There is a significant relationship between maternal age and parity with the incidence of Low Birth Weight (LBW) in the working area of UPT Batu Aji Public Health Center. Intensive education and monitoring of pregnancies among mothers with high-risk ages and low parity are required to reduce the incidence of LBW.